LEXICOSTATISTICS OF MALAY AND MALAGASY LANGUAGES: COMPARATIVE HISTORICAL LINGUISTIC STUDY - Wan Anayati; Muhammad Kiki Wardana; Mayasari Mayasari; Purwarno Purwarno (English Review: Journal of English Education, 2022)
This study examines the kinship of the Malay language and the Malagasy language. These two languages come from the same proto language, namely Proto Austronesian (PAN). Departing from the researchers’ assumptions about the linguistic relationship both at the phoneme and morpheme levels, there is a close kinship system or relationship between these two languages. Even though they are geographically and geo-politically separated, preliminary research on these two languages shows several universal features, one of which is that both languages are agglutinative languages. Therefore, this study is an attempt to find empirical evidence about the separation time between Malay and Malagasy by using language grouping methods and lexicostatistical techniques. The first stage, the researchers collect 300 basic vocabularies compiled by Swadesh (1995). The method used in providing the data is the referential method, while the technique used is the note-taking technique. Second, the researchers determine which pairs of the two languages are cognate languages. Third, the researchers calculate the age and separation time of the two languages. Fourth, the researchers calculate the error term to determine a more precise separation time. The result of this research indicates that Malay and Malagasy were a single language at 4223-3951 thousand years ago and began to separate from their proto languages in 2201-1929 BC.